Psychosocial interventions following self-harm in adults: a systematic review and meta-analysis - Hawton, Keith; Witt, Katrina G.; Taylor Salisbury, Tatiana L.; Arensman, Ella; Gunnell, David; Hazell, Philip; Townsend, Ellen; van Heeringen, Kees (Elsevier, 2016)
Background: Self-harm (intentional acts of non-fatal self-poisoning or self-injury) is common, often repeated and strongly associated with suicide. Effective aftercare of individuals who self-harm is therefore important. We have undertaken a Cochrane systematic review and meta-analysis of the effectiveness of psychosocial interventions for self-harm in adults. Methods: We searched five electronic databases (CCDANCTR-Studies and References, CENTRAL, MEDLINE, EMBASE, and PsycINFO) for randomised controlled trials (RCTs) of psychosocial interventions for adults following a recent (within six months) episode of self-harm. Fifty-five non-overlapping RCTs were identified. Most interventions were evaluated in single trials. We report results for interventions for which at least three RCTs comparing interventions to treatment as usual have been published and hence might contribute to clinical guidance. Findings: Cognitive behavioural-based psychotherapy (CBT; comprising cognitive-behavioural and/or problem-solving therapy) was associated with fewer participants repeating self-harm at six (OR 0·54, 95% CI 0·34 to 0·85; 12 trials; N=1,317) and 12 months’ follow-up (OR 0·80, 95% CI 0·65 to 0·98; 10 trials; N=2,142). There were also significant improvements in depression, hopelessness and suicidal ideation. Patients receiving dialectical behaviour therapy (DBT; three trials) had fewer repeat self-harm episodes post-intervention (MD -18·80, 95% CI -36·70 – -0·95; 3 trials; N=292), however, DBT was not associated with a significant reduction in the proportion of participants engaging in self-harm. Case management and sending regular postcards (four trials each) did not reduce repetition. Interpretation: CBT-based psychotherapy appears to be effective in patients following self-harm. DBT reduces frequency of repetition of self-harm. However, aside for CBT-based psychotherapy, there were few trials of other promising interventions, precluding firm conclusions as to their effectiveness.